Introduction to a poetics of diversity - Glissant, Édouard, 1928-2011 (Glissant Translation Project, 2020)
This book consists of four lectures and six interviews; it covers a wide range of topics central to Glissant's thought - such as creolization, langage, culture and identity, 'atavistic' versus 'composite cultures' - presented in a particularly accessible form because here Glissant interacts with the views of other people.